Developing a Cross-Platform Service Ordering Mobile Application for Social Integration - Cindrak, Emina; Ingvarsson, Anton; Jansson, Carl; Kanaan, Bassel; Karlsson, Christoffer; Sigvardsson, Martin (My University, 2017)
The aim of this project was to design and develop a cross-platform service ordering mobile application for Android and iOS. The application should enable clients to order services, and in turn, provide an easy way for newly arrived immigrants to find suitable tasks to perform, in order to enter the Swedish labour market. The application was developed on behalf of the company Just Arrived. The construction and development was focused on implementing the client part of the application and designing a visual prototype for the worker part. The client part enables clients to order simple services, such as lawn mowing or cleaning. These tasks are then published in the worker part of the application, used by newly arrived immigrants, to easily be found and applied for. This thesis describes the methodologies used, the theory behind the development and the design, the challenges confronted during the development process, and the final result of this project.
Keywords: Data- och informationsvetenskap; Computer and Information Science